Experimental study of sediment washout from stormwater sumps - Yang, Yunze (Water science and technology : a journal of the International Association on Water Pollution Research, 2022)
Sumps are commonly used in urban stormwater systems, which can be considered as a simple pretreatment device for stormwater quality control. However, they may function as pollution sources due to sediment washout under high flow conditions. An experimental study was conducted to investigate the scour process of predeposited sediments from a sump and its influencing parameters. Under conditions with large inflows or high sediment deposit, the sediment particles could be resuspended, entrained and flushed out. The washout mass decreased exponentially with time if the sediment bed surface depth was larger than a threshold value; otherwise, the amount of washout would be much smaller. The same scour pattern was observed for all the testing cases, of which the largest scour depth always occurred below the outlet. The deposit below the inlet might increase under conditions with high flow rates and low levels of sediment bed. Dimension analysis was performed and principal non-dimensional parameters were found, including the Péclet number, the pipe Froude number, and the dimensionless particle diameter, which can be used to determine whether the washout would occur and its intensity in a stormwater sump under given conditions